Do Criminal Sanctions Deter Insider Trading?. Issue 2 (4th April 2013) - Frijns, Bart; Gilbert, Aaron; Tourani‐Rad, Alireza
Abstract Many developed markets have taken what appears to be a tough stance on illegal insider trading through the use of criminal sanctions. Although criminal sanctions represent a much greater penalty than civil sanctions, the higher burden of proof required makes their enforceability weaker. This trade off between severity and enforceability makes the impact of criminal sanctions ambiguous. We empirically examine this issue by studying the deterrence of insider trading following the introduction of criminal sanctions in a developed market. Significant changes in sanction regimes are rare, especially when criminal sanctions are introduced without other changes. In February 2008, New Zealand introduced criminal sanctions for insider trading. This change of law offers a unique setting in which to examine the deterrence effect of criminalization. Using measures for the cost of trading, degree of information asymmetry, and probability of informed trading, we find that the enactment of this law led to a worsening in these measures. These findings suggest that the weaker enforceability of criminalization outweighs the associated increased severity of the penalties in New Zealand.